Bioinformatics analysis of andrographolide as an antisquamous cell carcinoma of the cervix - Raymond Devara; Sarmoko; Muhammad Salman Fareza (Fakultas Sains Institut Teknologi Sumatera, 2025)
Andrographolide, a natural substance isolated from Andrographis paniculata showing anticancer activity can be tested in silico to analyze its target in treatment of squamous cell carcinoma of the cervix. Objective of this study is dentifying andrographolide’s therapeutic target in treatment of squamous cell carcinoma of the cervix. Bioinformatics analysis was done by intersecting genes dysregulated in cancer and genes regulated by andrographolide. Potential therapeutic target genes activity related to cancer was analyzed and probable target genes were docked with andrographolide. Eighty three potential therapeutic target genes were identified and gene ontology and KEGG pathway analysis revealed their role in cancer. Target genes were further selected, resulted in three genes probable to be docked with andrographolide. Binding energy in kcal/mol between andrographolide and MAPK3, MMP9 and JAK2 respectively were -9.954, -9.470 and -8.482. Meanwhile, positive control binding energy were -10.050, -9.459 and -9.422. Andrographolide is shown to interact with a few key amino acid residues, such as Ile48 and Tyr53 in MAPK3, His230, His236, Pro246 and 247 in MMP9 and Leu983 in JAK2. In conclusion, MAPK3, MMP9 and JAK2 are potential therapeutic target genes for andrographolide within the treatment of squamous cell carcinoma of the cervix.